2020
DOI: 10.1038/s41598-020-69448-3
|View full text |Cite
|
Sign up to set email alerts
|

EEG dynamics and neural generators of psychological flow during one tightrope performance

Abstract: Psychological "flow" emerges from a goal requiring action, and a match between skills and challenge. Using high-density electroencephalographic (EEG) recording, we quantified the neural generators characterizing psychological "flow" compared to a mindful "stress" state during a professional tightrope performance. Applying swLORETA based on self-reported mental states revealed the right superior temporal gyrus (BA38), right globus pallidus, and putamen as generators of delta, alpha, and beta oscillations, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 84 publications
6
23
1
Order By: Relevance
“…While the frontal region was more active during guided imagery than in self-produced imagery, it was still less active than other brain regions, which might be explained by the transient hypofrontality hypothesis (Dietrich, 2003(Dietrich, , 2004Dietrich and Audiffren, 2011) as far as inhibition of activation within the prefrontal cortex (PFC) is concerned. Our results are also in line with the study of Leroy and Cheron (2020) who found a lack of frontal activity during flow conditions in the EEG recording of a tightrope professional in real action. Thus, imagery enhanced the automaticity of the subject's performance characteristic for the flow state (Harris et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…While the frontal region was more active during guided imagery than in self-produced imagery, it was still less active than other brain regions, which might be explained by the transient hypofrontality hypothesis (Dietrich, 2003(Dietrich, , 2004Dietrich and Audiffren, 2011) as far as inhibition of activation within the prefrontal cortex (PFC) is concerned. Our results are also in line with the study of Leroy and Cheron (2020) who found a lack of frontal activity during flow conditions in the EEG recording of a tightrope professional in real action. Thus, imagery enhanced the automaticity of the subject's performance characteristic for the flow state (Harris et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…CEN components) were found to be more active during flow. In contrast to the studies of Ulrich et al is the more recent study of Leroy and Cheron (2020), who studied brain activity in a professional tightrope performer. Their results were more in line with Dietrich's hypofrontality hypothesis.…”
Section: The Cen and Flowmentioning
confidence: 95%
“…Illustrative examples are highly skilled athletes, dancers or musicians who perform the acts that they have practiced intensively for so many times (e.g. Leroy & Cheron, 2020). Nevertheless, it is unlikely that flow is only related to the execution of well-learned behavioural or cognitive sequences because in that case it can be expected to occur only in routine tasks, which is not the case.…”
Section: The Cen and Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Today these visions have become reality and mobile EEG systems allow for the recordings of brain activity in everyday life situations, with much greater potential to treat a variety of disorders compared to lab-based research ( Debener et al, 2012 ). Mobile systems have been used in highly different settings, such as during physical activity ( Scanlon et al, 2019 ), in the work space ( Wascher et al, 2016 ), during driving ( Wang et al, 2018 ), and even while walking a tightrope ( Leroy and Cheron, 2020 ).…”
Section: Mobile Eeg and Recordings From The Earmentioning
confidence: 99%